At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's solve the problem of finding a quadratic polynomial whose sum and product of the zeros are given as [tex]\(\frac{8}{3}\)[/tex] and [tex]\(\frac{4}{3}\)[/tex] respectively. We'll then find the zeros of this polynomial using factorization.
### Step 1: Form the quadratic polynomial
Given:
- Sum of zeros [tex]\(\alpha + \beta = \frac{8}{3}\)[/tex]
- Product of zeros [tex]\(\alpha \cdot \beta = \frac{4}{3}\)[/tex]
A general quadratic polynomial whose zeros (roots) are [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex] can be written as:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
Using the properties of the sum and product of the roots of a quadratic polynomial:
- The sum of the roots [tex]\((\alpha + \beta) = -\frac{b}{a}\)[/tex]
- The product of the roots [tex]\((\alpha \cdot \beta) = \frac{c}{a}\)[/tex]
For simplicity, let's choose [tex]\(a = 3\)[/tex] to avoid fractions.
Now,
- From the sum of the roots: [tex]\(\frac{8}{3} = -\frac{b}{3}\)[/tex]
[tex]\[ b = -3 \cdot \frac{8}{3} = -8 \][/tex]
- From the product of the roots: [tex]\(\frac{4}{3} = \frac{c}{3}\)[/tex]
[tex]\[ c = 3 \cdot \frac{4}{3} = 4 \][/tex]
So, the quadratic polynomial is:
[tex]\[ 3x^2 - 8x + 4 = 0 \][/tex]
### Step 2: Factorize the polynomial to find the zeros
To find the zeros by factorization, let's try to rewrite the quadratic polynomial:
[tex]\[ 3x^2 - 8x + 4 \][/tex]
We need to find two numbers that multiply to [tex]\(3 \cdot 4 = 12\)[/tex] and add up to [tex]\(-8\)[/tex]. The numbers are [tex]\(-6\)[/tex] and [tex]\(-2\)[/tex].
So, we can rewrite the polynomial as:
[tex]\[ 3x^2 - 6x - 2x + 4 = 0 \][/tex]
Group the terms to factor by grouping:
[tex]\[ 3x(x - 2) - 2(x - 2) = 0 \][/tex]
Factor out the common term [tex]\((x - 2)\)[/tex]:
[tex]\[ (3x - 2)(x - 2) = 0 \][/tex]
### Step 3: Solve for the zeros
Set each factor equal to zero:
[tex]\[ 3x - 2 = 0 \quad \text{or} \quad x - 2 = 0 \][/tex]
Solving these:
[tex]\[ x = \frac{2}{3} \quad \text{or} \quad x = 2 \][/tex]
### Summary
The quadratic polynomial whose sum and product of the zeros are [tex]\(\frac{8}{3}\)[/tex] and [tex]\(\frac{4}{3}\)[/tex] respectively is:
[tex]\[ 3x^2 - 8x + 4 = 0 \][/tex]
The zeros of this polynomial are:
[tex]\[ x = \frac{2}{3} \quad \text{and} \quad x = 2 \][/tex]
### Step 1: Form the quadratic polynomial
Given:
- Sum of zeros [tex]\(\alpha + \beta = \frac{8}{3}\)[/tex]
- Product of zeros [tex]\(\alpha \cdot \beta = \frac{4}{3}\)[/tex]
A general quadratic polynomial whose zeros (roots) are [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex] can be written as:
[tex]\[ ax^2 + bx + c = 0 \][/tex]
Using the properties of the sum and product of the roots of a quadratic polynomial:
- The sum of the roots [tex]\((\alpha + \beta) = -\frac{b}{a}\)[/tex]
- The product of the roots [tex]\((\alpha \cdot \beta) = \frac{c}{a}\)[/tex]
For simplicity, let's choose [tex]\(a = 3\)[/tex] to avoid fractions.
Now,
- From the sum of the roots: [tex]\(\frac{8}{3} = -\frac{b}{3}\)[/tex]
[tex]\[ b = -3 \cdot \frac{8}{3} = -8 \][/tex]
- From the product of the roots: [tex]\(\frac{4}{3} = \frac{c}{3}\)[/tex]
[tex]\[ c = 3 \cdot \frac{4}{3} = 4 \][/tex]
So, the quadratic polynomial is:
[tex]\[ 3x^2 - 8x + 4 = 0 \][/tex]
### Step 2: Factorize the polynomial to find the zeros
To find the zeros by factorization, let's try to rewrite the quadratic polynomial:
[tex]\[ 3x^2 - 8x + 4 \][/tex]
We need to find two numbers that multiply to [tex]\(3 \cdot 4 = 12\)[/tex] and add up to [tex]\(-8\)[/tex]. The numbers are [tex]\(-6\)[/tex] and [tex]\(-2\)[/tex].
So, we can rewrite the polynomial as:
[tex]\[ 3x^2 - 6x - 2x + 4 = 0 \][/tex]
Group the terms to factor by grouping:
[tex]\[ 3x(x - 2) - 2(x - 2) = 0 \][/tex]
Factor out the common term [tex]\((x - 2)\)[/tex]:
[tex]\[ (3x - 2)(x - 2) = 0 \][/tex]
### Step 3: Solve for the zeros
Set each factor equal to zero:
[tex]\[ 3x - 2 = 0 \quad \text{or} \quad x - 2 = 0 \][/tex]
Solving these:
[tex]\[ x = \frac{2}{3} \quad \text{or} \quad x = 2 \][/tex]
### Summary
The quadratic polynomial whose sum and product of the zeros are [tex]\(\frac{8}{3}\)[/tex] and [tex]\(\frac{4}{3}\)[/tex] respectively is:
[tex]\[ 3x^2 - 8x + 4 = 0 \][/tex]
The zeros of this polynomial are:
[tex]\[ x = \frac{2}{3} \quad \text{and} \quad x = 2 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.